2012
DOI: 10.1194/jlr.r025882
|View full text |Cite
|
Sign up to set email alerts
|

AMP-activated protein kinase: an emerging drug target to regulate imbalances in lipid and carbohydrate metabolism to treat cardio-metabolic diseases

Abstract: This article is available online at http://www.jlr.org termed as metabolic syndrome (MetS) ( 1 ), characterized by a clustering of major risk factors for developing cardiovascular disease. Obesity, representing derangement in energy balances, is tightly linked with the development of type-2 diabetes through its ability to engender insulin resistance, leading to glucose intolerance and development of type-2 diabetes and dyslipidemia. Thus, insulin resistance The pathophysiology of diabetes and obesity is a very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
179
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 252 publications
(198 citation statements)
references
References 298 publications
(321 reference statements)
10
179
0
2
Order By: Relevance
“…Benefi cial effects of ETC-1002 on lipid and glucose metabolism have been demonstrated in multiple animal models and have been linked to ETC-1002-mediated activation of AMP-activated protein kinase (AMPK) (12)(13)(14)(15). AMPK represents an attractive therapeutic target, as it plays a fundamental role in maintaining cellular energy homeostasis via coordinating glucose and lipid metabolism as well as downregulating proinfl ammatory signaling pathways (16)(17)(18). In clinical studies, ETC-1002 has not only demonstrated improved lipid profi les but also revealed signifi cantly attenuated levels of hsCRP ( 19 ), an independent risk factor for CAD and a well-established clinical biomarker of infl ammation ( 20,21 ).…”
Section: Protein Arraysmentioning
confidence: 99%
See 2 more Smart Citations
“…Benefi cial effects of ETC-1002 on lipid and glucose metabolism have been demonstrated in multiple animal models and have been linked to ETC-1002-mediated activation of AMP-activated protein kinase (AMPK) (12)(13)(14)(15). AMPK represents an attractive therapeutic target, as it plays a fundamental role in maintaining cellular energy homeostasis via coordinating glucose and lipid metabolism as well as downregulating proinfl ammatory signaling pathways (16)(17)(18). In clinical studies, ETC-1002 has not only demonstrated improved lipid profi les but also revealed signifi cantly attenuated levels of hsCRP ( 19 ), an independent risk factor for CAD and a well-established clinical biomarker of infl ammation ( 20,21 ).…”
Section: Protein Arraysmentioning
confidence: 99%
“…Liver kinase B1 is an essential serine-threonine kinase that directly phosphorylates and activates AMPK ( 16,18,38,39 ). Previously, we have demonstrated that in HepG2 cells, …”
Section: Etc-1002 Activates Macrophage Ampk and Inhibits Immune Respomentioning
confidence: 99%
See 1 more Smart Citation
“…In most cells, including skeletal and cardiac muscle, liver, and adipose tissue, AMPK stimulates fatty acid oxidation, mitochondrial biogenesis, glucose transporter type 4 (GLUT4) translocation, and glucose uptake, while inhibiting protein synthesis, gluconeogenesis, and fatty acid and cholesterol synthesis (Steinberg and Kemp, 2009;Srivastava et al, 2012;Ruderman et al, 2013). Insulin secretion from pancreatic b-cells can be inhibited by AMPK (Steinberg and Kemp, 2009), and it has been shown that AMPK can increase food intake via activating signaling in the hypothalamus (Minokoshi et al, 2004).…”
Section: General Introductionmentioning
confidence: 99%
“…In mice fed with high-fat diet (HFD), absence of AMPKα2 in skeletal muscle subunit led to a development of glucose intolerance and insulin resistance [6]. AMPK is thus considered a therapeutic target in the prevention and treatment of T2DM [7][8][9]. Activation of AMPK in the liver and muscle is expected to elicit beneficial metabolic effects with the potential to improve the defects associated with T2DM and the metabolic syndrome [8].…”
Section: Introductionmentioning
confidence: 99%